2021
DOI: 10.1108/lht-03-2021-0100
|View full text |Cite
|
Sign up to set email alerts
|

No one left behind: risk communication to the street vendors during COVID-19 social distancing

Abstract: PurposeCOVID-19 presents a serious and unprecedented challenge around the globe. Street vendors are the most vulnerable group during this pandemic regarding livelihood loss and contagion risk. This research aims to examine the roles of risk communication work in enhancing COVID-19 risk perceptions and adoption of COVID-19 preventive behaviors among street vendors.Design/methodology/approachThe data were collected from the street vendors in urban Vietnam. A binary probit model was used for analyzing the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 70 publications
(98 reference statements)
0
27
0
Order By: Relevance
“…During social distancing, some cities have allowed street vendors—especially those selling fresh fruits and vegetables—to operate; however, most developing cities did not allow street vendors to work ( Chen, 2020 ; Guha et al, 2021 ; Lemessa et al, 2021 ; Sisay et al, 2021 ; Toriro & Chirisa, 2021 ). In urban Vietnam, the vendors were also required to suspend their businesses during social distancing ( Thanh et al, 2021 ; Turner et al, 2021 ). Already a vulnerable group, the pandemic pushed their economic live into further distress.…”
Section: The Covid-19 Pandemic In the World And In Vietnam: An Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…During social distancing, some cities have allowed street vendors—especially those selling fresh fruits and vegetables—to operate; however, most developing cities did not allow street vendors to work ( Chen, 2020 ; Guha et al, 2021 ; Lemessa et al, 2021 ; Sisay et al, 2021 ; Toriro & Chirisa, 2021 ). In urban Vietnam, the vendors were also required to suspend their businesses during social distancing ( Thanh et al, 2021 ; Turner et al, 2021 ). Already a vulnerable group, the pandemic pushed their economic live into further distress.…”
Section: The Covid-19 Pandemic In the World And In Vietnam: An Overviewmentioning
confidence: 99%
“…In developing cities worldwide, a large proportion of informal workers are street vendors, with the majority being women ( Jensen & Peppard, 2003 ; Lemessa et al, 2021 ; Muyanja et al, 2011 ; Thanh et al, 2021 ; Williams & Gurtoo, 2012 ). Street vendors sell various products, such as food, drinks, and other small items ( Chen, 2005 ; Jensen & Peppard, 2003 ; Lemessa et al, 2021 ; Romero-Michel et al, 2021 ; Sekhani et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They suggested public health policymakers could see public reaction via Twitter messages. The last paper on this topic, written by Thanh et al (2022), focused on risk communication in enhancing COVID-19 risk perceptions and adopting related preventive behaviour taken by street vendors in Vietnam. They showed that street vendors in Vietnam perceived high risks associated with COVID-19 and adopted preventive behaviour.…”
Section: Public Perception Of Covid-19 Vaccination and Social Distancingmentioning
confidence: 99%